(untitled) (Journal of Nuclear Technology in Applied Science, 2024)
This research is about studying the effect of adding some oxides, specifically cadmium and lead oxides at different substitution ratios to high-density polyethylene (HDPE) on the radiation protection properties of gamma rays. Based on this, we find that the polymer is characterized by the light weight of the protective material and increased flexibility in handling, while the lead and cadmium oxide fillings play their role as basic radiation attenuators in the polymer compound. High-density polyethylene (HD-PE) polymer composite samples filled with lead and cadmium oxides in the filler weight ratios of [5%, 10%, 15% and 20%) were prepared. Then, the HD-PE samples filled with (5% by weight, 10% by weight, 15% by weight, 20% by weight) micronized cadmium oxide and micronized PBO were charectrized using scanning electron microscopy (SEM). After that they were exposed to gamma rays emitted from radioactive point sources [241Am, 133Ba, 137Cs, and 60Co],in order to determine some parameter as leaner attenuation coefficients, mass attenuation coefficients, and half value layer for HDPE composites in the wide photon energy ranges ( 59.53, 80.99, 121.78, 244.69, 344.28, 356.01, 661.66, 778.90, 964.13, 1173.25, 1332.50, and 1408.01) KeV, respectively, which cover low and intermediate energy ranges and this was done using a highly pure germanium (HPGe) cylindrical detector. The obtained results for the shielding properties were compared with that for pure HDPE(without fillers) to study the effect of micro-CdO and micro-PbO content on the radiation shielding properties of HDPE. The measurements showed that HDPE filled with such oxides has good shielding properties for low and medium energy gamma rays. In addition, the experimentally measured values ​​were compared with that calculated theoretically ​​by XCOM program and the comparison showed a remarkable agreement between them.